TEACHING DRAWING LESSONS USING MODERN INTERACTIVE METHODS (International journal of artificial intelligence, 2025)
The article analyzes the significance of using modern interactive methods and technologies in teaching drawing, and their impact on students’ knowledge levels, thinking development, and efficiency of mastering the subject. Moreover, it elucidates opportunities offered by organizing lessons on the basis of digital technologies, and through visual and practical activities for forming students’ spatial imagination and technical thinking. Interactive approaches help students not only comprehend theory but also acquire deep practical skills in drawing.